2011
DOI: 10.1089/end.2011.0061
|View full text |Cite
|
Sign up to set email alerts
|

Variables That Influence Operative Time During Percutaneous Nephrolithotomy: An Analysis of 1897 Cases

Abstract: Presence of hydronephrosis, renal stone size and type significantly affect the operative time during PCNL. The duration of the operation was also observed to decrease with increased surgical experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 23 publications
3
34
0
1
Order By: Relevance
“…In another study, Akman et al found a cut-off point for blood transfusion as 58 min. The demonstrated predictive factors for bleeding were the number of access points, stone type (staghorn or other), diabetes mellitus, preoperative Hb level, and operation time of up to 58 min in their study (22). In the present study, if the operation time was longer than 90 min according to the ROC analysis, transfusion requirement and also bleeding risk would be increased (odds ratio = 8.03, relative risk = 5.2; Figure 1).…”
Section: Discussionmentioning
confidence: 46%
“…In another study, Akman et al found a cut-off point for blood transfusion as 58 min. The demonstrated predictive factors for bleeding were the number of access points, stone type (staghorn or other), diabetes mellitus, preoperative Hb level, and operation time of up to 58 min in their study (22). In the present study, if the operation time was longer than 90 min according to the ROC analysis, transfusion requirement and also bleeding risk would be increased (odds ratio = 8.03, relative risk = 5.2; Figure 1).…”
Section: Discussionmentioning
confidence: 46%
“…8,15,16,20,21 In other studies, stone surface area or stone size significantly affected complications and mean Clavien score. 3,17 Moreover, stone location, staghorn and complex stones had a significant influence on mean Clavien score, Clavien grades, or complications in some studies. 3,10,16,21,34 In other studies, stone distribution and staghorn stone had no significant effect on complications or grade ≥IIIa.…”
Section: Discussionmentioning
confidence: 99%
“…3,10,16,21,34 In other studies, stone distribution and staghorn stone had no significant effect on complications or grade ≥IIIa. 6,17 Puncturing, access and stone removal largely affect PCNL complications. 4 Stone characteristics may have eligible effects on the occurrence and severity of PCNL complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] The operation time is a good predictor of the surgical experience and the complexity of the case and is significantly affected by the stone size, location, multiplicity, calyceal anatomy and presence of hydronephrosis. [20] In this study, the impact of surgical experience can be ignored because all of the procedures were performed by a single experienced endourologist. It is also possible to ignore the stone location and multiplicity because these parameters were similar in both groups.…”
Section: Discussionmentioning
confidence: 99%